Kearifan Lokal Tanaman Legundi dalam Usaha Bumbu “Samba Itam” Khas Nagari Sulit Air Kabupaten Solok - Ikrimah Rhiza Mayesty; Eri Sayamar; Yulia Andriani (Politeknik Pertanian Negeri Payakumbuh, 2020)
This study aims to (1) Identify and describe of local wisdom that was, and is still done by the society in the collection of the seeds of vitex. (2) Identify and describe of local wisdom that ever existed and still do the community in the manufacture of seasonings black. (3) Identify and describe of local wisdom that was, and is still done by the society in the making “Samba Itam” as well as its application. This study using the technique of snowball sampling or chain by asking for information on people who have been interviewed or contacted previous and so on. The number of respondents in this study of 14 people with 3 key informants (key informants), 5 people collecting seeds legundi, 3 persons-entrepreneurs seasoning black and 3 persons-entrepreneurs “Samba Itam”. Based on the research results the conclusions obtained are (1) the local Wisdom of the plant legundi are still there and never there which is still carried on by the collecting society legundi amounted to 7 local wisdom, in the collection of the seeds of vitex there are 4 (14.29percents) and marketing of seeds of vitex as much as 3 (10,71percents) of the total of all local wisdom. (2) local Wisdom herbs black are still there and never there, which is still run by the society amounted to 12 local wisdom, seasoning black processing there is 10 (35,71percents) and marketing, there are 2 (7,14percents) of the total of all local wisdom. (3) local Wisdom Samba Itam are still there and never there, which is still run by the society amounted to 9 (32,14percents) of the total of all local wisdom.